2018
DOI: 10.1093/nar/gky1079
|View full text |Cite
|
Sign up to set email alerts
|

The BioGRID interaction database: 2019 update

Abstract: The Biological General Repository for Interaction Datasets (BioGRID: https://thebiogrid.org) is an open access database dedicated to the curation and archival storage of protein, genetic and chemical interactions for all major model organism species and humans. As of September 2018 (build 3.4.164), BioGRID contains records for 1 598 688 biological interactions manually annotated from 55 809 publications for 71 species, as classified by an updated set of controlled vocabularies for experimental detection method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
1,149
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,269 publications
(1,164 citation statements)
references
References 94 publications
(117 reference statements)
14
1,149
0
1
Order By: Relevance
“…Each organism appears to encode hundreds of Hero proteins with no apparent common motifs, and each Hero protein is likely to deal with many different client 1 6 proteins, thus providing a rich but complex source to mine. Indeed, Hero45, which was originally identified as an mRNA-binding protein (Heaton et al, 2001), has been found in the structure of the 80S ribosomes where it occupies the mRNA-binding channel (Habeck et al, 2013), but it is also known to be associated with hundreds of diverse proteins (Oughtred et al, 2019) with dynamic changes in its subcellular localizations in the cytoplasm, stress granules, nucleoli etc. (Lee et al, 2016(Lee et al, , 2014Yeom et al, 2015), highlighting the vast complexity of Hero proteins' actions.…”
Section: Discussionmentioning
confidence: 99%
“…Each organism appears to encode hundreds of Hero proteins with no apparent common motifs, and each Hero protein is likely to deal with many different client 1 6 proteins, thus providing a rich but complex source to mine. Indeed, Hero45, which was originally identified as an mRNA-binding protein (Heaton et al, 2001), has been found in the structure of the 80S ribosomes where it occupies the mRNA-binding channel (Habeck et al, 2013), but it is also known to be associated with hundreds of diverse proteins (Oughtred et al, 2019) with dynamic changes in its subcellular localizations in the cytoplasm, stress granules, nucleoli etc. (Lee et al, 2016(Lee et al, , 2014Yeom et al, 2015), highlighting the vast complexity of Hero proteins' actions.…”
Section: Discussionmentioning
confidence: 99%
“…Interaction network were generated using STRING's website (version 11.0) at high confidence (0.7) and network is clustered using a Markov Clustering algorithm “MCL inflation parameter = 3” (https://string-db.org/). BioGRID version 3.5.171 was used to extract known SCRIB and LANO interactors . The MS proteomics data, including search results, were deposited to the ProteomeXchange Consortium (http://www.proteomexchange.org) via the PRIDE partner repository with the dataset identifier PXD013636 and PXD013647.…”
Section: Methodsmentioning
confidence: 99%
“…Human protein-protein interactions (PPI) were downloaded from BioGRID version 3.3.123 (Oughtred et al, 2019) and non-physical interactions were removed, leaving 219,240 interactions. Additionally, an unweighted co-expression network of highly correlated genes, extracted from the GeneFriends co-expression map, was also used.…”
Section: Network Analysismentioning
confidence: 99%